A comparative assessment of knowledge, attitude, and practice of pharmacovigilance among medical, pharmacy, and nursing students in South-West Nigeria - Joseph Fadare; Theophilus Adegbuyi; Gbola Olayiwola; Ayobami Olusola; Ebisola Araromi; Iyanu Bankole; Juliet Olayinka; Abiola Obisesan (Babcock University Medical Journal)
Objective: To assess the knowledge and attitude of undergraduates in the discipline of medicine, pharmacy and nursing about adverse drug reactions and their reporting.